Atuação da defensoria pública como assistente de acusação frente ao novo papel do ofendido no processo penal - Silveira, Larissa Pedrolo (Universidade do Vale do Rio dos Sinos, 2011)
The position of victims in criminal proceedings was the subject of large imbalances of value throughout history, and is currently in a prominent position on the many legislative changes aimed at their protection and integration into the court system. The primary objective of this work is to analyze the influence of the new offense and how much can interfere with the operation of the Public Defender when it comes to the assistant to the prosecution. To this end, the first chapter presents an overview of the participation of the victim in criminal proceedings, from the origin to the recent criminal procedure reforms. In the next chapter expounds on existing discussions about the (un)constitutionality of the assistant to the prosecution. Finally, it explores the institutional role of the Ombudsman in this new conceptual paradigm of victim participation in order to establish criteria analysis can define whether or not a duty of action.
Keywords: Direito processual penal; Evolução do papel da vítima; Assistente de acusação; Atuação da defensoria pública; Criminal procedure law; Evolution of the role of victim; Assistant to the prosecution; Role of the public defender